The Implementation Of Spaced Repetition In Health Competency Exams Preparation A Systematic Review Of Various Models And The Impacts - Arianti Anaya; Yunia Wardi; Rino (Jurnal Riset Kesehatan, 2026)
Spaced repetition is a learning strategy in which material is reviewed at expanding intervals to strengthen retrieval and long-term memory. This systematic review evaluated spaced repetition in preparation for health competency examinations by examining test performance, knowledge retention, learner engagement, satisfaction, and implementation models. Searches were conducted in PubMed, ScienceDirect, Google Scholar, Scopus, Web of Science, and ERIC using Boolean combinations of "spaced repetition", "spaced learning", "distributed practice", "retrieval practice", "competency examination", "exam preparation", "test performance", "health education", "medical education", and "healthcare". Following PRISMA 2020 screening, 20 empirical studies published between 2015 and 2025 were included. The most notable result was that 14 studies (70.0%) reported significant improvement in examination or competency-related scores, 10 studies (50.0%) assessed retention beyond the immediate post-test, and 12 studies (60.0%) reported engagement metrics. However, 4 studies (20.0%) showed mixed or non-significant findings, indicating that effectiveness depends on intervention duration, content type, learner engagement, and curriculum support. Spaced repetition was generally more beneficial for factual, biomedical, and procedural knowledge than for complex clinical reasoning outcomes. Digital flashcards, scheduled low-stakes quizzes, analytics-based monitoring, and review blocks aligned with competency blueprints are practical pathways for curriculum integration. Further multi-institutional studies are needed to standardize implementation protocols and evaluate long-term transfer to clinical practice.